Hemorrhagic polycystic liver disease without the presence of polycystic kidney disease, a serious life-threatening condition: A case report. April 2015, Peru - Cárdenas Ruiz de Castilla, Daniel (2018)
Polycystic liver disease without the presence of polycystic kidney disease is a rare clinical condition and its hemorrhagic complication is even rarer, with very few cases being reported. It can be life-threatening without a rapid intervention. Case report: A 40 year-old female who presented with moderate sharp right upper quadrant abdominal pain and nausea for one hour. Emergency department: blood pressure 130/80 mmHg, heart rate 100 beats per minute, temperature 37 °C, O2 saturation 99 %, respiratory rate 22 breaths per minute. On examination, soft and relaxed abdomen, right upper quadrant abdominal pain, no visceromegaly, positive Murphy’s sign and rebound sign. Labs: hematocrit 34 %, hemoglobin 11.4 g/dL, white blood cells 12190, amylase 70 U/L. Abdominal ultrasound: Polycystic liver disease with ruptured cyst, abundant free subcapsular fluid within cavity, without pancreas and kidneys injury. Procedures: emergency exploratory laparoscopy, fluid drainage and aspiration, and partial cystectomy. Favorable evolution. Appointment with patient´s direct relatives for further studies.